PENGENDALIAN KUALITAS PADA PROSES CUTTING SEWING DENGAN MENGGUNAKAN METODE NINE TOOLS (Science and Technology (SciTech), 2023)
In the production process of making plastic sacks there are several processes, one of which is Cutting Sewing. Where Cutting Sewing is an automatic cutting and sewing process on plastic sacks. In this process, quality checks are carried out before packing, because if there is a defect in the sack it will affect the quality of the product produced. During the Cutting Sewing process, there are several criteria for defects, namely stringy/stretchy sacks, slanted cuts, and cropped images that exceed the target for defects. So that quality control can be carried out to find out how defective the process is. This study aims to determine the level of defects and causes of product defects produced. Using the Nine Tools Method, it will be known how many levels of defects and influences or problems that occur in the Cutting Sewing process. Nine tools are 9 quality tools that are used to determine the level of defects and problems as well as improvements regarding product defects with the aim that defects can be controlled. By using Control Chart P, Pareto Diagrams, Histograms, Scatter Diagrams, Fishbone, Stratification, Affinity Diagrams, Interrelationship Diagrams, and Tree Diagrams. The total production results are 312,318 pieces of plastic sacks with a total number of defects of 28,154 sheets. The results of the analysis showed that the highest defect rate occurred in the fibrous/drain sack with a total of 27709 defects or a 98.4% disability rate. There are several production defects that are not controlled and the distribution of the number of defects is not evenly distributed. The most common cause of defects is humans who are not careful because many requests are made and because the machines used are in poor performance.